2016
DOI: 10.18632/oncotarget.14468
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of lncRNA ANRIL up-regulates VEGF expression and promotes angiogenesis of diabetes mellitus combined with cerebral infarction by activating NF-κB signaling pathway in a rat model

Abstract: ObjectiveThis study aimed to explore the effects of lncRNA ANRIL on vascular endothelial growth factor (VEGF) and angiogenesis in diabetes mellitus (DM) combined with cerebral infarction (CI) through NF-κB signaling pathway.MethodsAdult male Wistar rats were randomly divided into control group and DM + CI group, and the DM + CI group were subdivided into Vector, shANRIL, PDTC, pcDNA-ANRIL, and pcDNA-ANRIL + PDTC groups. VEGF and FMS-like tyrosine kinase (FLT-1) expressions were measured by immunohistochemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
101
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 140 publications
(106 citation statements)
references
References 22 publications
3
101
0
2
Order By: Relevance
“…It has been observed that in cerebral infarction mouse models, miR‐145 can regulate the proliferation and migration of endothelial progenitor cells; moreover, miR‐210 was able to activate the NOTCH signaling and improve the angiogenesis after acute cerebral ischemia . VEGF is known as an angiogenic factor, and in the present study, we observed that the plasma levels of VEGF were significantly up‐regulated in patients with ACI, which was consistent with previous findings . More important, we first reported that the plasma level of miR‐99b was negatively correlated with the level of VEGF in patients with ACI, suggesting that down‐regulation of miR‐99b may be involved in the process angiogenesis in brain tissue after cerebral infarction.…”
Section: Discussionsupporting
confidence: 91%
“…It has been observed that in cerebral infarction mouse models, miR‐145 can regulate the proliferation and migration of endothelial progenitor cells; moreover, miR‐210 was able to activate the NOTCH signaling and improve the angiogenesis after acute cerebral ischemia . VEGF is known as an angiogenic factor, and in the present study, we observed that the plasma levels of VEGF were significantly up‐regulated in patients with ACI, which was consistent with previous findings . More important, we first reported that the plasma level of miR‐99b was negatively correlated with the level of VEGF in patients with ACI, suggesting that down‐regulation of miR‐99b may be involved in the process angiogenesis in brain tissue after cerebral infarction.…”
Section: Discussionsupporting
confidence: 91%
“…VEGF is an important angiogenic factor reported to induce the migration and proliferation of endothelial cells and enhance vascular permeability, thus accelerating endothelial injury . Zhang et al found that ANRIL regulated the expression of VEGF by activating the NF‐κB signalling pathway in a rat model of diabetes mellitus complicated by cerebral apoplexy . McArthur et al demonstrated that ANRIL regulated the expression of VEGF through recruiting PRC2 or p300 and regulating the expression of miR‐200b in a rat model of diabetes mellitus .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, increased lncRNA H19 expression is associated with impaired neurological function and increased TNF‐α level in AIS animal models . Antisense non‐coding RNA in the cyclin‐dependent kinase inhibitor 4 locus (ANRIL), an antisense lncRNA co‐clustered with p15/CDKN2B‐p16/CDKN2A‐p14/ARF, is overexpressed in cerebral infarction rat models and plays a pro‐inflammatory role by activating NF‐κB pathway . Likewise, lncRNA Gm4419 could activate NF‐κB pathway and contributes to cell damage in oxygen‐glucose–deprived cerebral microglial cells .…”
Section: Discussionmentioning
confidence: 99%
“…23 Antisense non-coding RNA in the cyclin-dependent kinase inhibitor 4 locus (ANRIL), an antisense lncRNA co-clustered with p15/CDKN2B-p16/CDKN2A-p14/ ARF, is overexpressed in cerebral infarction rat models and plays a pro-inflammatory role by activating NF-κB pathway. 24 Likewise, ln-cRNA Gm4419 could activate NF-κB pathway and contributes to cell damage in oxygen-glucose-deprived cerebral microglial cells. 25 Another in vitro and in vivo study discloses that lncRNA SNHG14 elevates the expression of pro-inflammatory factors (such as TNF-α and nitric oxide), thereby aggravating neuron damage by regulating miR-145-5p/PLA2G4A.…”
Section: Discussionmentioning
confidence: 99%